Gut-Brain cross talk: The pathogenesis of neurodevelopmental impairment in necrotizing enterocolitis - Manohar, Krishna; Mesfin, Fikir M.; Liu, Jianyun; Shelley, W. Christopher; Brokaw, John P.; Markel, Troy A. (Frontiers in Pediatrics, 2023)
Necrotizing enterocolitis (NEC) is a devastating condition of multi-factorial origin that affects the intestine of premature infants and results in high morbidity and mortality. Infants that survive contend with several long-term sequelae including neurodevelopmental impairment (NDI)—which encompasses cognitive and psychosocial deficits as well as motor, vision, and hearing impairment. An alteration in the gut-brain axis (GBA) homeostasis has been implicated in the pathogenesis of NEC and the development of NDI. The crosstalk along the GBA suggests that microbial dysbiosis and subsequent bowel injury can initiate systemic inflammation which is followed by pathogenic signaling cascades with multiple pathways that ultimately lead to the brain. These signals reach the brain and activate an inflammatory cascade in the brain resulting in white matter injury, impaired myelination, delayed head growth, and eventual downstream NDI. The purpose of this review is to summarize the NDI seen in NEC, discuss what is known about the GBA, explore the relationship between the GBA and perinatal brain injury in the setting of NEC, and finally, highlight the existing research into possible therapies to help prevent these deleterious outcomes.